Fast experiments for structure elucidation of small molecules: Hadamard NMR with multiple receivers. (25th August 2015) - Gierth, Peter; Codina, Anna; Schumann, Frank; Kovacs, Helena; Kupče, Ēriks; Giraudeau, Patrick
<x xml:space="preserve">Abstract</x> We propose several significant improvements to the PANSY (Parallel NMR SpectroscopY) experiments—PANSY COSY and PANSY‐TOCSY. The improved versions of these experiments provide sufficient spectral information for structure elucidation of small organic molecules from just two 2D experiments. The PANSY‐TOCSY‐Q experiment has been modified to allow for simultaneous acquisition of three different types of NMR spectra—1D C‐13 of non‐protonated carbon sites, 2D TOCSY and multiplicity edited 2D HETCOR. In addition the J‐filtered 2D PANSY‐gCOSY experiment records a 2D HH gCOSY spectrum in parallel with a 1J‐filtered HC long‐range HETCOR spectrum as well as offers a simplified data processing. In addition to parallel acquisition, further time savings are feasible because of significantly smaller F1 spectral windows as compared to the indirect detection experiments. Use of cryoprobes and multiple receivers can significantly alleviate the sensitivity issues that are usually associated with the so called direct detection experiments. In cases where experiments are sampling limited rather than sensitivity limited further reduction of experiment time is achieved by using Hadamard encoding. In favorable cases the total recording time for the two PANSY experiments can be reduced to just 40 s. The proposed PANSY experiments provide sufficient information to allow the CMCse software package (Bruker) to solve structures of small organic molecules. Copyright © 2015 John Wiley & Sons, Ltd.